Influence of Myeloid-derived Suppressor Cells in Tumor Immunotherapy - Yu, Yang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The immunosuppressive response of myeloid-derived suppressor cells (MDSCs) in tumor microenvironment (TME) has become an important area of tumor research. Among them, arginase 1 (ARG1), as a key immunosuppressive molecule in MDSCs, inhibits T cell function by consuming L-arginine, producing polyamines and secreting immunosuppressive cytokines, thereby promoting tumor immune escape. This article first briefly introduces the background and mechanism of action of MDSCs, and then systematically summarizes and analyzes the fine regulation of ARG1 expression by multiple factors, including transcriptional, epigenetic and post-translational mechanisms, and its specific role in MDSCs and its regulatory mechanism. Finally, the research progress of ARG1 as a potential therapeutic target is summarized, such as the development and application of ARG1 inhibitors, and the mechanisms of action and advantages and disadvantages of several different research methods are analyzed. A promising small molecule inhibitor CB-1158 and future prospects are understood, and the therapeutic direction and possible solutions for future research are proposed.